2020
DOI: 10.3389/fcell.2020.598020
|View full text |Cite
|
Sign up to set email alerts
|

miR-7-5p Affects Brain Edema After Intracerebral Hemorrhage and Its Possible Mechanism

Abstract: Objective: To explore the relationship between miR-7-5p and brain edema after intracerebral hemorrhage and the role of butylphthalide (NBP) in brain edema after intracerebral hemorrhage.Method: Routine blood testing, C-reactive protein results, and computed tomography data were collected 1, 7, and 14 days after intracerebral hemorrhage in six patients. Levels of MMP-9, ZO-1, occludin, IL-6, TNF-α, and miR-7-5p were detected in each patient's serum. Sixty male Sprague–Dawley rats were randomly divided into sham… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 52 publications
(71 reference statements)
0
12
0
Order By: Relevance
“…Previously, we confirmed that the neuroprotective effect of NBP may be related to inhibiting the expression of TNF-α and MMP-9, and down-regulating oxidative stress and DNA damage after ICH 18 . Meanwhile, other studies suggested that NBP can up-regulated the expression of VEGF and angiopoietins-2 (Ang-2) proteins 36 , and decreased the expression of AQP4 37 . Collectively, the cellular and molecular mechanism of NBP protection in ICH includes promoting neovascularization, attenuating inflammation response, and decreasing brain edema.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we confirmed that the neuroprotective effect of NBP may be related to inhibiting the expression of TNF-α and MMP-9, and down-regulating oxidative stress and DNA damage after ICH 18 . Meanwhile, other studies suggested that NBP can up-regulated the expression of VEGF and angiopoietins-2 (Ang-2) proteins 36 , and decreased the expression of AQP4 37 . Collectively, the cellular and molecular mechanism of NBP protection in ICH includes promoting neovascularization, attenuating inflammation response, and decreasing brain edema.…”
Section: Discussionmentioning
confidence: 99%
“… Zhang et al (2020b) observed that inhibition of the expression of AQP4 with glycyl-l-histidyl-l-lysine (GHK) could alleviate the injury of astrocytes and brain edema. Moreover, a different group also showed that AQP4 deletion reduced brain edema ( Chen et al, 2020 ).…”
Section: The Change In Aqp4 Expression After Strokementioning
confidence: 99%
“…It has also been proven as protective against ischemiareperfusion injury in in vivo rat models by some [49], and as aggravating by others [50]. A recent study demonstrated that miR-7-5p was decreased in the serum of patients suffering from hemorrhagic stroke [51]. Should the results extrapolated from rats be accurate, this would mean a diminished inhibition the PI3K/AKT pathway, leading to an increase of aquaporin 4 (AQP4) within the brain edema area caused by the hemorrhage.…”
Section: Mir-7-5pmentioning
confidence: 99%